LncRNA TUG1 promoted viability and associated with gemcitabine resistant in pancreatic ductal adenocarcinoma - Fan Yang; Xiaofang Li; Lingjuan Zhang; Lina Cheng; Xiuling Li (Elsevier, 2018)
Objective: To investigate the underlying mechanism of lncRNA TUG1 in pancreatic ductal adenocarcinoma (PDAC). Methods: The expression of TUG1 was defined by qRT-PCR. The apoptotic cells were detected by flow cytometry assay. The cell migration and invasion were measured by scratch assay and Transwell assay. The level of ERK pathway was detected using Western blot. Results: Compared with normal tissues and cells, the expression of TUG1 was up-regulated in pancreatic cancer tissue and cells. Meanwhile, knockdown of TUG1 could promote PDAC cells apoptosis and inhibit PDAC cells viability, migration and invasion. In addition, overexpression of TUG1 enhanced the gemcitabine chemoresistance of PDAC cells. Surprisingly, gemcitabine combined with SCH772984 (a suppressor of ERK pathway) could reverse the drug resistance resulted from overexpression of TUG1. Conclusion: TUG1 promoted the viability of PDAC cells and enhanced its resistance of gemcitabine. Keywords: LncRNA TUG1, PDAC, Oncogenic, Gemcitabine resistance